Regulating Alternative Healing in France, And the Problem of ‘Non-Medicine’ - Cloatre, Emilie (Med Law Rev, 2019)
This article explores the ambiguities of the legal system that, in France, regulates ‘alternative healing’, and determines the boundaries of legitimate medical care. While the law suggests that the delivery of therapeutic care should be the monopoly of biomedically-trained professionals, alternative healers operate very widely, and very openly, in France. They practice, however, on the verge of (il)legality, often organising their activities, individually and collectively, so as to limit the likelihood of state intervention. This creates a high degree of precarity for both practitioners and, crucially, for patients. Efforts to change the system are being deployed, but while healers themselves have increasingly organised to seek recognition by the state, alternative healing occupies an uncertain policy space: they are not fully constituted as a social and policy matter by the state, and occupy a liminal position between medicine and spirituality that “unsettles” republican ideals of scientific rationality, and of secularism. This article explores some of those tensions, at the crossroad between law, science, and medicine. It reflects on why tensions seem to persist around the regulatory questions at stake, and suggests that ways forward may depend on moving away from science as a sole arbiter in drawing boundaries of legitimate and illegitimate care in regulation.